2017
DOI: 10.1126/science.aan0032
|View full text |Cite
|
Sign up to set email alerts
|

Wild emmer genome architecture and diversity elucidate wheat evolution and domestication

Abstract: Wheat (Triticum spp.) is one of the founder crops that likely drove the Neolithic transition to sedentary agrarian societies in the Fertile Crescent more than 10,000 years ago. Identifying genetic modifications underlying wheat’s domestication requires knowledge about the genome of its allo-tetraploid progenitor, wild emmer (T. turgidum ssp. dicoccoides). We report a 10.1-gigabase assembly of the 14 chromosomes of wild tetraploid wheat, as well as analyses of gene content, genome architecture, and genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
746
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 714 publications
(769 citation statements)
references
References 56 publications
(35 reference statements)
18
746
1
4
Order By: Relevance
“…Recent genetic studies have shown the potential for these wild species to provide useful genetic variation for grain weight that could possibly have been excluded from the gene pool during domestication (Golan et al ; Arora et al ; Avni et al ). The genome sequences and other genomic resources now available for many of these progenitor species and landraces will aid the identification of these novel genes and alleles (Avni et al ; Luo et al ; Wingen et al ).…”
Section: Interactionsmentioning
confidence: 99%
“…Recent genetic studies have shown the potential for these wild species to provide useful genetic variation for grain weight that could possibly have been excluded from the gene pool during domestication (Golan et al ; Arora et al ; Avni et al ). The genome sequences and other genomic resources now available for many of these progenitor species and landraces will aid the identification of these novel genes and alleles (Avni et al ; Luo et al ; Wingen et al ).…”
Section: Interactionsmentioning
confidence: 99%
“…Btr1/Btr2, identified by their role in domestication of barley and wheat (Pourkheirandish et al, 2015;Avni et al, 2017), encode proteins with unknown functions. IND orthologues are confined to the Brassicaceae, indicating neofunctionalisation of IND in AZ development of that family (Pab on-Mora et al, 2014).…”
Section: Divergent Gene Co-expression Network In a Conserved Backgroundmentioning
confidence: 99%
“…Multiple different wheat and wheat relative genome sequences have been published, including the genomes of the wild progenitors of hexaploid bread wheat: T. urartu (Ling et al ; Ling et al ), Aegilops tauschii (Jia et al ; Luo et al ; Zhao et al ; Zimin et al ) and T. turgidum ssp. dicoccoides (Avni et al ). The release of the emmer genome assembly is of great importance because it highlights the relative ease of sequencing wild relatives in the Triticeae and, due to high collinearity, future genome assemblies will benefit from pre‐existing references.…”
Section: Genomic Resources and Reference Sequencementioning
confidence: 99%
“…In barley, there are two closely linked non‐brittle rachis genes, Btr1 and Btr2 , which have been cloned in the homoeologous region on chromosome 3H, although they only appear to be related to each other functionally and not structurally (Pourkheirandish et al ). None of the Br genes have been cloned in wheat, although Avni et al () have provided evidence, at the DNA sequence level, that the Br genes are responsible for the non‐shattering phenotype in wheat through loss‐of‐function variants in the Btr homologs.…”
Section: Introductionmentioning
confidence: 99%